Customer engagement in Acehnese traditional restaurants: Mediating effects on revisit intention and e-WOM - Mahdani Ibrahim; Halimatussakdiah Halimatussakdiah; M. Ridha Siregar; Ghrina Zikran; Rido Amalia; Dicky Pratama Putra (Innovative Marketing)
This study examines the influence of restaurant attributes on customer engagement with traditional food products (TFP), and how this engagement affects revisit intention and electronic word-of-mouth (e-WOM). Conducted from January to September 2024 in Banda Aceh and Aceh Besar, Indonesia, the study surveyed 160 customers who had dined at traditional Acehnese restaurants. Data were collected using a structured questionnaire based on a five-point Likert scale and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results reveal that Food Quality (β = 0.323; p < 0.001), Staff Service (β = 0.256; p < 0.001), Health Involvement (β = 0.219; p = 0.013), and Involvement in Luxury (β = 0.282; p < 0.001) significantly enhance TFP Engagement. In contrast, Convenience Orientation does not show a significant effect. Moreover, TFP Engagement strongly predicts Intention to Revisit (β = 0.877; p < 0.001) and positive e-WOM (β = 0.757; p < 0.001), acting as a mediator between restaurant attributes and customer behavioral outcomes.